Acute isolated dislocation of the distal radial ulnar joint – ulnar volar with no other associated lesion: Case report and review of the literature - N. Naim Rodriguez; A. Verdini Gasti; C. Mesoraca; F. Pierobon (Trauma Case Reports, 2022)
Isolated dislocation of the distal radioulnar joint is a rare phenomenon with few described cases in the literature for which the management is not well established. We report here a case of distal radioulnar joint dislocation – ulnar volar. The patient is a 58-year-old woman who fell on an extended upper extremity with forced supination. The patient was treated non-surgically with closed reduction and immobilization followed by physical and ergonomic therapy. During treatment MRI imaging was performed which showed no lesion to the TFCC. Following immobilization, the patient had good mobility of the forearm and the wrist. Early diagnosis, treatment, and imaging allowed for excellent functional recovery without surgical treatment.